Bio-oil and bio-char production from corn cobs and stover by fast pyrolysis - Mullen, Charles A.; Boateng, Akwasi A.; Goldberg, Neil M.; Lima, Isabel M.; Laird, David A.; Hicks, Kevin B. (Biomass & bioenergy, 2010)
Bio-oil and bio-char were produced from corn cobs and corn stover (stalks, leaves and husks) by fast pyrolysis using a pilot scale fluidized bed reactor. Yields of 60% (mass/mass) bio-oil (high heating values are ∼20 MJ kg −1, and densities >1.0 Mg m −3) were realized from both corn cobs and from corn stover. The high energy density of bio-oil, ∼20–32 times on a per unit volume basis over the raw corn residues, offers potentially significant savings in transportation costs particularly for a distributed “farm scale” bio-refinery system. Bio-char yield was 18.9% and 17.0% (mass/mass) from corn cobs and corn stover, respectively. Deploying the bio-char co-product, which contains most of the nutrient minerals from the corn residues, as well as a significant amount of carbon, to the land can enhance soil quality, sequester carbon, and alleviate environmental problems associated with removal of crop residues from fields.